The crime decline in cross-national context: a panel analysis of homicide rates within latent trajectory groups. Issue 3 (3rd July 2021) - Tuttle, James; McCall, Patricia; Land, Kenneth
ABSTRACT: During the 1990s, the United States and other wealthy democracies experienced a decline in homicide rates. However, not all nations shared this trend. Despite disparate homicide patterns, researchers usually examine the average effect of correlates on homicide, potentially obscuring the impact of heterogeneity within large samples. The current study addresses this implicit homogeneity assumption by identifying three distinct latent trajectory groups of homicide trends among 77 nations from 1989 to 2010. To examine differences in the correlates of homicide trends, we analyse the impact of demographic and economic influences on homicide rates in separate fixed-effects panel regression analyses for each trajectory group as well as for the overall sample. We find that demographic and economic forces impact homicide rates differently across subsets of nations. Our findings suggest that universal explanations of 1990s cross-national homicide trends are misleading, as the same set of factors influence homicide rates differently across national contexts.